Foreign Direct Investment-A Boon For Indian Retail Industry - Ghufran, Ali; Ali, Arif (Gyan Management Journal, 2013)
Indian retail sector is highly fragmented as more than 90% of its business being carried out by traditional family runs small stores, which provides immense opportunity for large scale retailers to set-up their operations and alters the retailing landscape in India. Indian retail sector which accounts for 10% of the country's Gross Domestic Product (GDP) and contributes to 8% of the total employment is expected to grow from US$ 395.96 billion in 2012 to US$ 785.12 billion by 2015. The present paper is an attempt to get an ins
Keywords: FDI; Organized and Unorganized retail; PDS; Hypermarket; Supermarket; Convenience store; Shopping Mall